Evaluation of Soil Revegetation Success Rate Ex-Pit Coal Mine in Kitadin site Embalut Kutai in East Kalimantan. - I Gede Eka Budiana; Jumani Jumani; Maya Preva Biantary (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2017)
PT. Kitadin Embalut Site is one of mining companies in Kutai Kartanegara Regency of East Kalimantan Province with total concession area 2,973 ha. Coal mining activities, both directly and indirectly impact on decreasing the environmental quality include pollution of water, air, noise, soil damage, damage to vegetation and wildlife disturbance and optimize reclamation activities. The objective of this study to evaluate the implementation of the success rate of reclamation and revegetation implemented Kitadin Embalut site. The type of research is descriptive, observation data collection and primer documents.Tool of research including: brunton compass, measuring tape, Suunto clinometer, Gauges, plastic rope. Vegetation analysis performed using a circular swath diameter of 17.8 m. The number of plots generated for each year of planting is 1 (one) with a distance of between 50-100 meters plot, the plot would be carried out observations of plant growth on the whole plant is located on the plot example, height, diameter, and canopy closure , For parameters where local species and wildlife presence also performed on this plot.The results of this study illustrate the level of success of revegetation in PT. Kitadin Embalut site in 2010, 2011, and 2012 with growth rates with an average diameter is 22.3 cm, 18 cm and 10 cm. High average in 2010, 2011, and 2012 is 12.8 meters, 8.3 meters and 6.5 meters. Canopy closure rates are in 2010.2011 and 2012 crop year was 71.2%, 60.6%, 53.4%, percentage of growth in 2010.2011 and 2012 at 88%, 77.7%, 83.6%.Based on the indicators of the success rate of growth in both diameter and height it can be concluded that the reclamation and revegetation in PT. Kitadin Embalut site considered good. In addition it should also be increased monitoring of overall plant growth so the company has a data base of all levels petumbuhan existing plants in the area PT. Kitadin Embalut site.